Management of novel oral anticoagulants in emergency and trauma surgery. Issue 4 (August 2016) - Pinho-Gomes, Ana-Catarina; Hague, Adam; Ghosh, Jonathan
Abstract: Background: The compelling safety, efficacy and predictable effect of novel oral anticoagulants (NOACs) is driving a rapid expansion in their therapeutic indications. Management of the increasing number of patients on those new agents in the setting of emergency or trauma surgery can be challenging and the absence of specific reversal agents has been a matter of concern. This review summarises the key principles that underpin the management of those patients with a particular emphasis on the recent development of specific antidotes. Findings: As of 2015, a new line of antidotes, specific for these drugs, are at different stages of their development with their release imminent. However, as NOACs are innately reversible due to their short half-life, the use of reversal agents will probably be restricted to a few exceptional cases. Post-marketing surveillance will be paramount to better clarify the role of these promising drugs. Conclusions: Management of patients on NOACs in the context of emergency or trauma surgery relies on best supportive care in combination with the blood products and/or specific antidotes as required. Familiarity with the new reversal agents is essential but further evidence on their indications, safety and efficacy as well as consensus guidelines are warranted prior to widespread adoption.